Att balansera barnets åsikter och barnets bästa - En kvalitativ studie om socialsekreterares arbete i spänningsfältet mellan barnets åsikter och skyddsbehov - Gustafsson,Agnes; Irme,Selma (2026)
This study aimed to examine how social workers work with children’s right to be heard and with assessments of the best interests of the child in social services investigations, as well as how they manage the tension between these two principles. The study adopted a qualitative approach and is based on semistructured interviews. The participants consisted of six investigative social workers from different municipalities in Sweden. The ones we interviewed all worked with children within social services. The results of the study show that social workers address children’s right to be heard through adapted child interviews, relationship-building efforts, and collaboration with other actors within the child’s network, but that children’s influence over decision-making varies. Assessments of the best interests of the child are characterized by considerable professional discretion, where the child’s need for protection is often prioritized over the child’s expressed wishes and opinions, particularly when those wishes may place the child’s safety at risk. The results highlight a lack of established guidelines for managing this tension when the child’s right to be heard does not align with what is assessed as the child’s best interests. As a result, social workers must make their own interpretations and judgments regarding how these principles should be balanced. When children’s views cannot be accommodated, social workers emphasize the importance of transparency and providing explanations directly to the child. In summary, the study concludes that children’s right to be heard is formally ensured, but that needs-based assessments grounded in risk and protection ultimately play a decisive role. Overall, the study indicates that children’s right to be heard is formally ensured, while assessments of the child’s best interests are primarily based on evaluations of risk and protection needs.
Keywords: the best interests of the child; children’s right to be heard; the social services’ investigative work; the Convention on the Rights of the Child; participation